Estimation of sex using discriminant function analysis of percutaneous finger lengths in Nepalese adults - Walung, Eugen Dolma; Maharjan, Mani Raj; Shrestha, Rijen (Journal of Kathmandu Medical College, 2019)
Background: Disasters are a common occurrence in Nepal. This necessitates the development of baseline forensic anthropological data specific to the Nepalese population. Recent advances in the field of forensic medicine and sciences have somewhat reduced the relevance of forensic anthropology in the western developed world. The financial burden of these newer techniques, however, puts emphasis back on methodological examination of remains to establish identity. Objectives: To establish the sex of the individual from the percutaneous length of the fingers. Methodology: One hundred and twenty medical students (58 males and 62 females) were randomly selected and their finger lengths measured. These measurements were analyzed to establish discriminant functions to estimate sex. Results: The equation derived was Y = (1.822 x Left index finger length) + (1.141 x Left little finger length) – 19.211. Group centroids were calculated to be -0.933 for females and 0.998 for males. The sensitivity was found to be 76.9% and a specificity of 78.2%. Overall, the function correctly classified 77.5% of the original cases. Conclusion: Based on these findings, finger length is as reliable in estimation of sex of an individual as other longs bones and can be an ideal tool for examination, especially in remains where the skull and pelvis are absent or missing.